Activity of β-Lactam Antibiotics Against Pseudomonas aeruginosa Carrying R Plasmids Determining Different β-Lactamases - Jacoby, George A. (1979)
Azlocillin, carbenicillin, cefsulodin, mezlocillin, nocardicin A, piperacillin, pirbenicillin, sulbenicillin, and ticarcillin, but not HR756, showed reduced activity against Pseudomonas aeruginosa strains producing seven types of β-lactamase.